A retrospective study on bacteriology, clinicopathologic and radiographic features in 28 cats diagnosed with pyothorax - Sim, Juin Jia; Lau, Seng Fong; Omar, Sharina; Watanabe, Malaika; Aslam, Muhammad Waseem (Multidisciplinary Digital Publishing Institute, 2021)
This retrospective study aimed to determine the etiological, clinicopathological, and radiographic features and outcome of feline pyothorax cases. Medical records from twenty-eight cats with pyothorax aged from 4 months to 10 years (median 10 months) diagnosed between 2013 and 2020 were reviewed. Dyspnoea (75.0%), abnormal lung sounds (75.0%) and open-mouth breathing (64.3%) were the predominant respiratory signs. Leucocytosis (61.5%), particularly monocytosis (68.0%), and hyperglobulinaemia (65.4%) were among the most prominent findings in blood analysis. Bilateral pleural effusion was found in 67.9% of the thoracic radiographs. A total of 47.4% of the cytological samples revealed the presence of bacteria, while all had positive bacterial growth. Pasteurella multocida, E. coli, Streptococcus spp., and Staphylococcus spp. were the predominant aerobic bacteria isolated from pleural effusion samples. A chest tube was placed in 64.3% of the cats and 66.7% of cats with chest tubes survived. In total, 46.4% of cats with pyothorax recovered. Amoxicillin–clavulanate was the antimicrobial of choice against aerobic bacteria found in this study and should be given in combination with antimicrobials that cover anaerobic bacteria. Chest tube placement is crucial for treatment success. Cytological results and bacterial culture may not be consistent; thus, bacterial culture should be performed for every case.